An integrated vendor-buyer model subject to supply disruption with transportation cost / Noraida Azura Md Darom ... [et al.] - Md Darom, Noraida Azura; Hishamuddin, Hawa; Ramli, Rizauddin; Mat Nopiah, Zulkifli; A Sarker, Ruhul (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
A combined proactive and reactive approach to deal with disruption in the supply chain (SC) is presented in this paper, where an optimization model that is capable of determining the optimal safety stock level and optimal recovery schedule for a serial two-stage SC system was developed. The system considered in the study consists of a single vendor and a single buyer, subject to random supply disruption. The vendor keeps extra inventory as safety stock to be used at the time of disruption as to minimize stock-outs. In addition, the effect of transportation cost to the recovery model is investigated. The developed problem is solved using the branch-and-bound algorithm and numerical analysis is conducted to show the applicability of the model. The results indicate that the optimal safety stock level is not significantly influenced by short disruption time and primarily affected by holding cost value. It can be emphasized that within the same number of recovery cycles, the increase of setup cost and ordering cost will increase the optimal safety stock quantity. On the other hand, an increase in holding cost will decrease the optimal safety stock quantity. This paper contributes to the literature on supply disruption recovery and safety stock inventory decisions.